2014
DOI: 10.1210/me.2014-1217
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ Signaling Promotes Juvenile Granulosa Cell Tumorigenesis by Suppressing Apoptosis

Abstract: Molecular changes that give rise to granulosa cell tumors of the ovary are not well understood. Previously, we showed that deletion in granulosa cells of the bone morphogenetic protein receptor-signaling transcription factors, Smad1 and Smad5, causes development of metastatic granulosa cell tumors that phenocopy the juvenile form of granulosa cell tumors (JGCTs) in humans. The TGFβ-SMAD2/3 pathway is active in JGCTs, but its role is unknown. We tested the in vivo contribution of TGFβ-SMAD signaling to JGCT dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 59 publications
0
35
0
1
Order By: Relevance
“…Because canonical BMP signaling activity is attenuated in Smad1/5 conditional knockout mice, disruption of the Smad4 gene in this model is expected to further block SMAD4-dependent TGFB/activin signaling. It is interesting to note that tumors developed in Smad1/5/4 triple conditional knockout mice are not metastatic but are prone to apoptosis [41]. These findings support that TGFB signaling promotes the proliferation of granulosa cells [4244].…”
Section: Tgfb Superfamily Signaling In Gct Development: Lessons From mentioning
confidence: 86%
See 2 more Smart Citations
“…Because canonical BMP signaling activity is attenuated in Smad1/5 conditional knockout mice, disruption of the Smad4 gene in this model is expected to further block SMAD4-dependent TGFB/activin signaling. It is interesting to note that tumors developed in Smad1/5/4 triple conditional knockout mice are not metastatic but are prone to apoptosis [41]. These findings support that TGFB signaling promotes the proliferation of granulosa cells [4244].…”
Section: Tgfb Superfamily Signaling In Gct Development: Lessons From mentioning
confidence: 86%
“…Interestingly, ovaries from Smad1/5 and Bmpr1a/Bmpr1b conditional knockout mice express high levels of TGFB downstream target genes such as TGFB induced ( Tgfbi ) and matrix metallopeptidase 2 ( Mmp2 ) and/or harbor SMAD2/3 activation, in concordance with the antagonism between TGFB and BMP signaling pathways [10, 11, 39, 40]. Generation of Smad1/5/4 triple conditional knockout mice by the Pangas laboratory further indicates that SMAD4-dependent TGFB/activin signaling may be tumorigenic in the mouse ovary [41]. Because canonical BMP signaling activity is attenuated in Smad1/5 conditional knockout mice, disruption of the Smad4 gene in this model is expected to further block SMAD4-dependent TGFB/activin signaling.…”
Section: Tgfb Superfamily Signaling In Gct Development: Lessons From mentioning
confidence: 99%
See 1 more Smart Citation
“…Antagonism between signaling by the TGFβ/activin and BMP families of ligands has been reported in numerous developmental processes (30)(31)(32) and tissues (33)(34)(35)(36)(37)(38). Dysregulation of this antagonism can have dramatic consequences for tissue homeostasis, as seen in juvenile granulosa cell tumors, in which mouse models have shown that tumorigenesis is promoted by TGFβ/activin signaling through SMAD2/3 and is opposed by BMP signaling through SMAD1/5 (39)(40)(41)(42)(43)(44)(45)(46)(47). Direct competition between the pathways can occur for availability of the shared type 2 receptors ACVR2A/B (48)(49)(50) or the availability of the common cofactor SMAD4 (51).…”
Section: (A) Expression Ofmentioning
confidence: 99%
“…Recent molecular and immunohistochemical (IHC) analyses of AGCTs indicate that FOXL2 is a central transcription factor in the ovary and that with GATA4 and phosphorylated SMAD2/3 (pSMAD2/3) are likely key players in tumor growth (26 -28, 33, 34). Mouse models that develop GCTs have been generated (10,31,(35)(36)(37)(38)(39)(40) and have provided important clues about factors controlling GCT formation. In particular, the wingless type mouse mammary tumor virus integration site family (WNT)/␤-catenin and TGF␤/activin/SMAD pathways appear to be factors involved in GCT formation (10,(37)(38)(39)(40), although none of the current mouse models completely recapitulate the molecular phenotype of AGCTs in women.…”
mentioning
confidence: 99%